THU0223 Treatment of a patient with nonclassified hla b27 associated destructive oligoarthritis with anti tnf: clinical outcome and effects on nf-kappa b activity in pbmc. (1st June 2001) - Geiler, T; Voll, R; Lorenz, HM; Dechant, C; Manger, B; Kalden, JR
Abstract : Background: We report the case of a 38 years old HLA B27 positive male with a 11 year history of a destructive nonclassified oligoarthritis. While the first 6 years of the disease have been dominated by a relapsing nondestructive synovitis of the right knee joint and a asymptomatic sacroileitis treated with NSAID`s alone the disease began to spread in a destructive manner to the right wrist and foot (MTP I-V, PIP I-V, DIP I-V). Additionally, a painful tenosynovitis of the flexor and extensor tendons of both feet occured. Despite intensifying the pharmacological treatment by high doses of corticosteroides (up to 100 mg/d) and methotrexate (25 mg/week) for 9 month the disease showed significant clinical and radiological progress. No reduction of the constantly elevated ESR and CRP could be achieved. By initiating a therapy with anti TNF (Remicade TM ) at a dose of 5 mg/kg body weight all clinical symptoms disappeared completely within 8 h after the first infusion of the antibody. ESR and CRP normalised within 6 days. The patient stayed completely free of symptoms since, side effects have not been detected by now. Repeated infusions after 2, 4, 6 and 14 weeks did not further improve the therapeutic benefit but were given to sustain the therapeutic effect. Objectives: Since TNF is known as a strong activator of NF-κB which is strongly involved in the production of proinflammatory cytokines and matrix metalloproteinases we looked for the activity of this transcription factor in PBMC`s of this patient by electro mobility shift assays (EMSA). Methods: Cells were obtained immediately before the infusions were started and 1 h and 24 h after end of infusions. Cell preparations and EMSA were done according standard protocols. Results: There was substantial NF-κB activity in PBMC`s before first antibody treatment. Anti TNF treatment decreased NF-κB activity detectable already 1 h after first infusion. The NF-κB activity was further inhibited 24 h after first infusion and remained low during the whole treatment period in accordance to the persisting clinical improvement. Conclusion: In the treatment of patients with progressive nonclassified HLA B27 oligoarthritis resistent to classical treatment with NSAID`s, corticosteroids and DMARD`s the use of TNF blocking agents should be considered. As in other destructive inflammatory joint diseases NF-κB might play a crucial role in the pathogenesis of joint destruction in HLA B27 associated arthritides. The clinical improvement appears to be associated with a persistent and marked inhibition of NF-kappa B.